Asymmetric Organocatalytic Michael Addition–Cyclisation Cascade of Cyclopentane-1,2-dione with Alkylidene Malononitriles - Silm, Estelle; Kaabel, Sandra; Järving, Ivar; Kanger, Tõnis (Synthesis, 2019)
An asymmetric organocatalytic cascade reaction between cyclopentane-1,2-diones and alkylidene malononitriles affords highly substituted 4H-pyrans in moderate to high enantiomeric excess. The selective reduction of a bridged double bond leads to the formation of cis-substituted cyclopentanone with three contiguous stereogenic centres.
Keywords: organocatalysis; asymmetric catalysis; diketone; pyran; cascade reaction